Analysis of AKAP7γ Dimerization. (31st August 2015) - Singh, Arpita; Rigatti, Marc; Le, Andrew V.; Carlson, Cathrine R.; Moraru, Ion I.; Dodge-Kafka, Kimberly L.
Abstract : A-kinase anchoring proteins (AKAPs) constitute a family of scaffolding proteins that contribute to spatiotemporal regulation of PKA-mediated phosphorylation events. In particular, AKAP7 is a family of alternatively spliced proteins that participates in cardiac calcium dynamics. Here, we demonstrate via pull-down from transfected cells and by direct protein-protein association that AKAP7 γ self-associates. Self-association appears to be an isoform specific phenomenon, as AKAP7 α did not associate with itself or with AKAP7 γ . However, AKAP7 γ did associate with AKAP7 δ, suggesting the long isoforms of the AKAP can form heterodimers. Surface plasmon resonance found that the AKAP7 γ self-association occurs via two high affinity binding sites withK D values in the low nanomolar range. Mapping of the binding sites by peptide array reveals that AKAP7 γ interacts with itself through multiple regions. Photon counting histogram analysis (PCH) of AKAP7 γ -EGFP expressed in HEK-293 cells confirmed that AKAP7 γ -EGFP self-associates in a cellular context. Lastly, computational modeling of PKA dynamics within AKAP7 γ complexes suggests that oligomerization may augment phosphorylation of scaffolded PKA substrates. In conclusion, our study reveals that AKAP7 γ forms both homo- and heterodimers with the long isoforms of the AKAP and that this phenomenon could be an important step in mediating effective substrate phosphorylation in cellular microdomains.